pH-responsive theranostic nanoplatform of ferrite and ceria co-engineered nanoparticles for anti-inflammatory - Dou, Yuanyao; Zhang, Yimin; Lin, Caiyu; Han, Rui; Wang, Yubo; Wu, Di; Zheng, Jie; Lu, Conghua; Tang, Liling; He, Yong (Frontiers in Bioengineering and Biotechnology, 2022)
Integrating multiple components to achieve both therapy and diagnosis in a single theranostic nanosystem has aroused great research interest in the medical investigator. In this work, a novel theranostic nanoplatform ferrite and ceria co-engineered mesoporous silica nanoparticles (Fe@Ce-MSN) antioxidant agent was constructed by a facile metal Fe/Ce-codoping approach in MSNs framework. This resulted Fe3+-incorporated ceria-based MSN nanoparticles that possess a higher Ce3+ to Ce4+ ratio than this revealed by ceria only nanoparticles. The as-prepared Fe@Ce-MSN nanoparticles exhibited an excellent efficiency of scavenging reactive oxygen species (ROS), which is attributed to the improvement of superoxide dismutase (SOD) mimetics activity by increased Ce3+ content and maintains a higher activity of catalase (CAT) mimetics via inclusion of ferrite ion in nanoparticles. The fast biodegradation of Fe@Ce-MSNs, which is sensitive to mild acidic microenvironment of inflammation, can lead to accelerating Fe/Ce ions releasing, and the freed Fe ions enhanced T2-weighted magnetic resonance imaging in inflammation site. In vitro cell models, PEGylated Fe@Ce-MSN nanoparticles significantly attenuated ROS-induced inflammation, oxidative stress, and apoptosis in macrophages by scavenging overproduced intracellular ROS. Thus, the novel pH-responsive theranostic nanoplatform shows great promise in ROS related pneumonia disease treatment.